High-performance aluminum-based brazing filler metal and preparation method thereof

By optimizing the composition and preparation method of aluminum-based brazing, the wetting, fluidity, joint strength, thermal conductivity and corrosion resistance of the brazing material are improved, and the problem of insufficient performance of traditional brazing material in the high-end manufacturing field is solved, and the development of high-performance aluminum-based brazing material is realized.

CN119635078AActive Publication Date: 2025-03-18YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1

Patent Information

Application Number
CN202411962709.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Traditional aluminum-based solder has shortcomings in wetting, fluidity, joint strength, thermal conductivity and corrosion resistance in the high-end manufacturing field, making it difficult to meet high-performance needs.

Method used

A high-performance aluminum-based solder is adopted, and its composition includes 5-15 wt% silicon, 1-8 wt% copper, 0.2-2 wt% rare earth elements, 0.02-0.5 wt% trace elements, 0.3-3 wt% nanoreinforced phase and Al margin. By optimizing the proportion of each component and the preparation method, the comprehensive performance of the solder is improved.

Benefits of technology

It significantly improves the wettability, fluidity, joint strength, thermal conductivity and corrosion resistance of the solder, and can meet the high-performance requirements in the field of high-end precision manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119635078A_ABST
    Figure CN119635078A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of brazing materials, in particular to high-performance aluminum-based brazing filler metal and a preparation method thereof.The high-performance aluminum-based brazing filler metal comprises the following components of 5-15 wt% of silicon, 1-8 wt% of copper, 0.2-2 wt% of rare earth elements, 0.02-0.5 wt% of microelements, 0.3-3 wt% of nanometer reinforcing phases and the balance Al; the rare earth element is a composition of lanthanum, cerium and neodymium; the microelement is a composition of titanium, zirconium, boron and vanadium; the nano reinforced phase is a composition of nano aluminum oxide and nano silicon carbide; the preparation method comprises the steps of raw material preparation, composite smelting, melt-spinning and post-treatment. The aluminum-based brazing filler metal provided by the invention has excellent wettability, flowability, joint strength, thermal conductivity and corrosion resistance; the preparation method provided by the invention is relatively short in production period, energy-saving, consumption-reducing, stable, controllable, high in preparation efficiency and low in preparation cost, the market competitiveness of the material is favorably improved, and the large-scale requirement in the field of high-end precision manufacturing is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing materials, in particular to a high-performance aluminum-based brazing filler metal and a preparation method thereof. Background Art

[0002] As an important connection technology, brazing is widely used to connect metal materials to achieve structural assembly and functional integration. With the continuous advancement of science and technology, especially in high-end fields such as aerospace, rail transportation, automobile manufacturing and electronic devices, the performance requirements of brazed joints are becoming increasingly stringent.

[0003] Traditional aluminum-based solders have many limitations in practical applications and are difficult to meet the high-performance requirements of high-end manufacturing, such as: (1) Wettability. Traditional aluminum-based solders have poor spreading performance on the surface of the parent material, resulting in the formation of welded joints that are not firm and uniform, seriously affecting the welding quality. In the aerospace field, the welding of parts requires extremely high precision and reliability. The insufficient wettability of traditional solders may cause welding defects and endanger flight safety. (2) Fluidity. Fluidity is also a shortcoming of traditional aluminum-based solders. When facing narrow welds, not only is the weld filling rate low, but it is also difficult to fully fill. In the manufacture of electronic devices, the welding of tiny parts requires the solder to accurately fill small spaces to ensure the stability and reliability of circuit connections. Obviously, the low fluidity of traditional aluminum-based solders cannot meet this requirement. (3) Strength. The joint strength of traditional aluminum-based solders is limited. They are prone to failure when subjected to large load stresses, and cannot guarantee the stability and reliability of welded structures under complex working conditions. In the field of automobile manufacturing, the operation of vehicles will generate various vibrations and shocks. Insufficient strength of welded joints may cause parts to loosen or break, affecting the performance and safety of the vehicle. (4) Thermal conductivity. The thermal conductivity of traditional aluminum-based solder is relatively low. The heat dissipation efficiency is not high during operation, and heat is easily accumulated, which leads to a decline in material performance or structural damage. For electronic devices, overheating will affect their performance and life, so there are high requirements for the thermal conductivity of the solder. Traditional aluminum-based solder is difficult to meet the requirements of high thermal conductivity. (5) Corrosion resistance. This is also a significant problem of traditional aluminum-based solder. In harsh corrosive environments, such as marine engineering, chemical industry and other fields, traditional aluminum-based solder is easily corroded, shortening its service life and increasing maintenance costs. For example, equipment in marine engineering is exposed to high-salinity and high-humidity environments for a long time. The corrosion problem of traditional aluminum-based solder will seriously affect the reliability and durability of the equipment.

[0004] In order to meet the needs of high-end precision manufacturing, it is urgent to develop an aluminum-based brazing filler metal with excellent wettability, fluidity, joint strength, thermal conductivity, corrosion resistance, etc. For this purpose, this application is proposed. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the background technology, the present invention provides a high-performance aluminum-based solder and a preparation method thereof, which are used to solve the problems in the prior art that the wettability, fluidity, joint strength, thermal conductivity, corrosion resistance, etc. cannot meet the use requirements in the high-end precision manufacturing field.

[0006] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0007] On the one hand, the present invention provides a high-performance aluminum-based brazing filler metal, comprising the following components: 5-15wt% silicon, 1-8wt% copper, 0.2-2wt% rare earth elements, 0.02-0.5wt% trace elements, 0.3-3wt% nano-reinforced phase, and Al balance;

[0008] The rare earth element is a combination of lanthanum, cerium and neodymium;

[0009] The trace elements are a combination of titanium, zirconium, boron and vanadium, with a titanium-zirconium content ratio of 1:(0.5-1) and a boron-vanadium content ratio of 1:(0.3-2);

[0010] The nano-reinforced phase is a composition of nano-aluminum oxide and nano-silicon carbide, and the content of nano-aluminum oxide in the nano-reinforced phase is 30-70wt%.

[0011] Copper plays an important role in improving the strength and thermal conductivity of solder joints. Precisely controlling the copper content can reduce the amount used and control production costs while maintaining the strength and thermal conductivity of the solder. The addition of silicon can significantly improve the fluidity of the solder. The improvement of the fluidity of the solder promotes the enhancement of the spreadability and filling of the solder. At the same copper content, it is more conducive to better performance of copper strength and thermal conductivity.

[0012] The introduction of silicon is mainly used to enhance the fluidity of the solder during the brazing process. It provides a good liquid flow foundation, making it easier for the solder to flow and fill in the part to be welded. However, the introduction of silicon will increase the brittleness of the solder. For this reason, the present invention strictly controls its content range to 5-15wt%, and optimizes the copper content to 1-8wt%. The copper content is greatly reduced compared with the prior art, so the production cost is significantly reduced; moreover, within the above range, the synergistic effect of copper and aluminum can optimize the fluidity of the solder, improve the spreadability and filling properties, and at the same time enhance the strength of the welded joint, better adapt to complex weld structures, and make up for the brittle defects caused by silicon;

[0013] The addition of rare earth elements has a significant effect on improving the performance of solder in many aspects, especially in improving wettability, oxidation resistance and joint strength. During the solidification process of solder, rare earth elements such as lanthanum La, cerium Ce, neodymium Nd react with the main alloying elements aluminum Al, silicon Si, and copper Cu to generate a variety of high-strength and high-hardness intermetallic compound phases including LaAl3, CeSi2, NdCu2, etc. These intermetallic compound phases are dispersed in the welded joint and can effectively hinder the movement of dislocations, thereby significantly improving the tensile strength of the welded joint, fully meeting the stringent requirements of high-end precision manufacturing for high strength and high stability of welded joints.

[0014] The trace elements are a combination of titanium, zirconium, boron and vanadium. The combination of titanium and zirconium in a limited ratio helps to refine the grains of the solder and enhance its corrosion resistance; the synergistic effect of boron and vanadium in a limited ratio can enhance the high temperature resistance of the solder, so that the solder can still maintain good performance under high temperature conditions;

[0015] The introduction of nano-reinforced phase can further improve the mechanical properties of the solder. By interacting with other alloy elements at the microstructural level, it can also help to further overcome the brittleness problem after the introduction of silicon and improve the corrosion resistance of the product, thus comprehensively optimizing the overall performance of the solder.

[0016] Aluminum is the base material and accounts for the largest proportion in the solder. It has the excellent properties of light weight and high thermal conductivity, providing basic physical performance support for the entire solder system and is a key factor in achieving good thermal conductivity and lightweight requirements of the solder in practical applications.

[0017] The components exist simultaneously and work synergistically in the above proportions to obtain a high-performance aluminum-based brazing filler metal with good comprehensive properties including wettability, fluidity, joint strength, thermal conductivity, and corrosion resistance, which can meet the requirements of use in the field of high-end precision manufacturing.

[0018] Preferably, the composition comprises the following contents: 8-12wt% silicon, 3-6wt% copper, 0.5-1.5wt% rare earth elements, 0.15-0.5wt% trace elements, 1-2wt% nano-enhanced phase, and the balance Al;

[0019] Among the rare earth elements, the content ratio of lanthanum, cerium and neodymium is (2-3):(3-4):(2-3);

[0020] Among the trace elements, the total content of titanium and zirconium is 0.2-0.4wt%, the total content of boron and vanadium is 0.1-0.3wt%, and the titanium-zirconium content ratio is 1:(0.6-0.7), and the boron-vanadium content ratio is 1:(0.9-1.1). It is particularly preferred that the titanium-zirconium content ratio is 1.5:1 and the boron-vanadium content ratio is 1:1.

[0021] On the basis of the previous embodiment, the present invention continues to optimize the proportion of each component and confirms that the product meeting this content requirement has stronger strength and better fluidity.

[0022] Preferably, the rare earth element content is 0.5-1.2wt%, the total titanium and zirconium content in trace elements is 0.3-0.45wt%, and the titanium and zirconium content ratio is 1:(0.8-0.9).

[0023] After rare earth elements are added, while improving wettability, oxidation resistance, and joint strength, the corrosion resistance of the solder can also be improved. It is speculated that this may be related to the various intermetallic compound phases generated by them, or it may be synergistic with other elements such as aluminum, copper, and silicon, and the corrosion resistance is improved through microstructures such as purifying grain boundaries. Titanium and zirconium in trace elements can form a stable oxide film that covers the surface of the solder, preventing the corrosive medium from contacting the matrix, thereby improving corrosion resistance; in addition, titanium and zirconium may also affect the microstructure of the alloy, making the grain boundaries more stable, which is then conducive to further improving corrosion resistance. The present invention unexpectedly found that when the rare earth element content is 0.5-1.2wt% and the total titanium and zirconium content in the trace elements is 0.3-0.45wt%, and the titanium-zirconium content ratio is 1:(0.8-0.9), the corrosion resistance of the resulting product is better.

[0024] Preferably, the copper content is 5-7 wt%.

[0025] The copper content plays an important role in improving the thermal conductivity of aluminum-based solder. Aluminum, as a matrix material, has high thermal conductivity itself, which provides a basic guarantee for the thermal conductivity of the solder. The presence of copper can increase the heat conduction channel and improve thermal conductivity. The synergistic effect of copper and aluminum can significantly improve the thermal conductivity of the solder. The present invention has discovered through creative labor that when the copper content is 5-7%, its synergistic effect with aluminum is most obvious, and the thermal conductivity of the solder obtained at this time is particularly excellent.

[0026] Further preferably, the nano-reinforced phase is a composition of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 1:1, and the average particle sizes of the nano-aluminum oxide and the nano-silicon carbide are both 10-100 nm.

[0027] Theoretically, the smaller the particle size of nano-alumina and nano-silicon carbide, the better their performance. However, too small a particle size will lead to poor dispersibility, which is not conducive to improving performance. Therefore, the average particle size of nano-alumina and nano-silicon carbide is controlled to 10-100nm, which can take into account both dispersibility and the improvement of product mechanical properties after addition.

[0028] The present invention optimizes the types and proportions of the components in the aluminum-based solder to obtain an aluminum-based solder with good comprehensive performance that can meet the needs of the high-end precision manufacturing field. The high-performance aluminum-based solder is lightweight, environmentally friendly, and recyclable. Compared with the prior art, it has at least the following beneficial effects:

[0029] (1) Good wettability, its spreading area is significantly improved. During the brazing process, the brazing material can spread better on the surface of the base material, forming a stronger and more uniform weld joint, effectively improving the welding quality.

[0030] (2) It has good fluidity and can fill narrow welds. For welds with a width of 0.15 mm, its filling rate is as high as over 90%. Therefore, it has obvious advantages when used for welding complex structures or tiny parts, and can ensure the integrity and sealing of the welds.

[0031] (3) The joint strength is high. The tensile strength of the joint is significantly improved, which can reach 280-325MPa. The high-strength welded joint can withstand greater load stress, ensuring the stability and reliability of the welded structure during use, and can better meet the high-end precision manufacturing field with higher strength requirements.

[0032] (4) Good thermal conductivity. Its good thermal conductivity helps it to dissipate heat in time during operation and prevents material performance degradation or structural damage caused by heat accumulation. It is especially suitable for electronic devices and other fields with high heat dissipation requirements.

[0033] (5) Excellent corrosion resistance. When tested in a simulated marine environment, its corrosion rate is very low. Its excellent corrosion resistance enables it to work stably for a long time in a harsh corrosive environment, extending its service life and reducing maintenance costs, thereby meeting the needs of use in aerospace, marine engineering and other fields with high requirements for corrosion resistance.

[0034] On the other hand, the present invention also provides a method for preparing a high-performance aluminum-based solder, comprising the following steps: S1, raw material preparation; S2, composite smelting; S3, strip throwing; S4, post-processing.

[0035] Preferably, in step S1, the sources of silicon, copper and aluminum are silicon blocks, copper blocks and aluminum blocks respectively, the source of rare earth elements is a lanthanum-cerium-neodymium alloy block, the source of trace elements is titanium powder, zirconium powder, boron powder and vanadium powder, and the source of nano-reinforced phase is nano-alumina powder and nano-silicon carbide powder; the silicon block, copper block, aluminum block and lanthanum-cerium-neodymium alloy block are first pretreated and then accurately weighed according to the stoichiometric ratio, and the pretreatment includes a process to improve the purity of the raw materials and / or a process to activate the surface state of the raw materials.

[0036] In this embodiment, the powder corresponding to the trace elements is preferably micron-sized and nano-sized, such as titanium powder and zirconium powder with an average particle size of 1-10 μm, and boron powder and vanadium powder with an average particle size of 0.5-5 μm. Smaller particle sizes can ensure better performance and uniform dispersion in the solder, and fully contact and react with other elements, so as to better play its role in grain refinement and performance enhancement. It is preferred to perform additional ball milling treatment on the powder of the trace elements to further refine the particle size and improve its activity, which is conducive to better dispersion and alloying during the smelting process.

[0037] Preferably, in step S2, the composite smelting includes arc melting and vacuum induction melting, firstly, an arc with a current of 400-1000A and a voltage of 15-35V is used to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, and then the pre-melted alloy liquid is poured into a cooling mold, cooled at a cooling rate of 30-150°C / s to obtain a pre-alloyed ingot, and then the pre-alloyed ingot is crushed and vacuum induction melting is performed, during vacuum induction melting, the temperature is first raised to 750-850°C and kept warm for 5-30min, and then the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements are slowly added in sequence, and electromagnetic stirring is turned on, the stirring rate is 300-800Hz, the magnetic field strength is 0.05-0.3T, and the temperature is kept warm for 25-65min to obtain the solder liquid;

[0038] The organic dispersion of the nano-reinforced phase and the organic dispersion of the trace elements are obtained by ultrasonically dispersing the nano-reinforced phase and the trace elements in an organic solvent, respectively. The organic solvent contains only C, H and O elements.

[0039] In this embodiment, during arc melting, the vacuum is first evacuated to 10 -3 -10 -5 Pa, and then high-purity argon (purity ≥ 99.99%) is charged to a furnace pressure of 0.01-0.05MPa, the arc current is adjusted to 400-1000A, the arc voltage is adjusted to 15-35V, and the remaining raw materials except trace elements and nano-enhanced phases are melted at a stirring rate of 30-120rpm to obtain a pre-melted alloy liquid. The specific melting time depends on the total amount of raw materials involved in the melting. Generally speaking, 50-200g of raw materials requires about 15-25min. Within this time range, the raw materials can be fully melted and preliminarily alloyed, and at the same time, there will be no excessive energy consumption and possible component segregation problems due to too long a time. If the total amount of raw materials is insufficient or exceeds the above range, the corresponding melting time can be shortened or extended accordingly.

[0040] In this embodiment, during vacuum melting, the vacuum is first evacuated to 10 -4 -10 -5Pa, and then fill with ultra-high purity argon (purity ≥ 99.99%) as protective gas, the argon flow rate is precisely controlled at 3-15L / min, the high vacuum environment can further remove gas impurities in the pre-alloyed ingot, the precisely controlled argon flow rate can not only protect the alloy from oxidation, but also maintain a stable atmosphere in the furnace, and then the furnace temperature is raised to 750-850°C at a heating rate of 6-16°C / min, and kept at this temperature for 5-30min to partially melt the pre-alloyed ingot. At this time, the pre-prepared organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements are successively injected into the alloy liquid in the furnace at a slow speed through a precision injection device, and at the same time, the electromagnetic stirring is strengthened, the stirring frequency is increased to 300-800Hz, and the magnetic field strength is 0.05-0.3T. Under this condition, the nanoparticles can be uniformly dispersed in the alloy liquid to avoid the occurrence of agglomeration; then continue to keep at this temperature for 25-65min, so that the nanoparticles and the alloy are fully fused and homogenized, thereby obtaining a solder alloy with more stable performance and uniformity.

[0041] It should be noted that:

[0042] (1) The organic dispersion of the nano-reinforced phase and the organic dispersion of the trace elements are ultrasonically dispersed in an organic solvent containing only C, H, and O elements, such as alcohols and ketone solvents. In order to improve the uniformity of the dispersion, a small amount of surfactant can also be added. The constituent elements of the surfactant should not contain high-temperature non-volatile elements as much as possible to avoid introducing undesigned impurity elements into the system. The organic solvent containing only C, H, and O is also a preferred embodiment based on not introducing impurities. Of course, the organic solvent can also be selected from other organic solvents other than those in the embodiments of the present invention. Due to the high vacuum and high temperature during vacuum melting, the organic solvent will volatilize in large quantities, and a series of subsequent post-treatments will also reduce residual impurities.

[0043] (2) The organic dispersion of the nano-enhanced phase is injected first, preferably at a speed of 0.5-6 ml / min; the organic dispersion of the trace elements is injected later, preferably at a speed of 0.5-2 ml / min, and the organic dispersion of the trace elements is injected more slowly.

[0044] The main function of the nano-reinforced phase is to further improve the mechanical properties of the solder by interacting with other alloy elements at the microstructural level. In the smelting process, the early addition of the nano-reinforced phase allows it to interact with the matrix elements at the early stage of the alloy liquid formation, and utilizes its nanoscale characteristics to better disperse and form a good bonding interface with the matrix. In the subsequent insulation process, its reinforcing effect is fully exerted, and the microstructure of the alloy is optimized, such as grain refinement and uniformity improvement, laying a good microstructural foundation for the subsequent addition and synergy of trace elements. The total amount of trace elements is relatively small, and its main function is to refine the solder grains, enhance corrosion resistance and high temperature resistance through a specific proportion. In order to ensure its uniform distribution, it needs to be added at a slower injection rate. Adding trace elements more slowly after the nano-reinforced phase has begun to interact with the alloy matrix and form a certain microstructure can make the trace elements more accurately play their synergistic role with other elements on the basis of the optimized microstructure. For example, Ti and Zr can further optimize the grain structure on the basis of the nano-reinforced phase to enhance the stability of the grain boundary and improve the corrosion resistance; B and V can better play their high temperature resistance in the microstructure environment improved by the nano-reinforced phase, thereby achieving synergistic effects between the elements and jointly improving the comprehensive performance of the solder. If the trace elements are added first, they may not be able to fully play their synergistic role with other elements due to their low content and uneven distribution in the alloy liquid, and may affect the uniform dispersion of the nano-reinforced phase in the alloy liquid and the bonding effect with the matrix.

[0045] Preferably, in step S3, the strip is spun by means of a rapid solidification strip-spinning device, and the technical parameters of the strip-spinning are: the copper roller linear speed is 25-40 m / s, the injection pressure is 0.15-0.5 MPa, and the solder liquid superheat is 60-140°C, and finally a solder thin strip with a thickness of 20-50 μm and a thickness tolerance within ±3 μm is obtained.

[0046] Preferably, in step S4, the post-treatment includes: removing the surface oxide film, cleaning, drying under vacuum or inert gas protection and aging treatment, and the temperature of the aging treatment is 120-250° C. and the time is 2-10 hours.

[0047] In this embodiment: the specific operation of removing the surface oxide film can be: first soak the thin strip in a room temperature alkaline solution of pH 7-9 for 3-15 minutes to remove the slight oxide film on the surface, improve the cleanliness of the thin strip surface, and provide good surface conditions for subsequent processing. The specific operation of cleaning can be: rinse with deionized water 2-6 times to thoroughly remove impurities such as residual alkaline solution, ensure the purity of the thin strip surface, and prevent impurities from having adverse effects on the performance of the solder. The specific operation of drying can be: low-temperature drying at 60-120°C under the protection of high-purity nitrogen to remove moisture, ensure that the thin strip is in a dry state, and prevent moisture from causing adverse chemical reactions in subsequent aging treatment and other processes. The specific operation of aging treatment can be: place it in an oven at a temperature of 120-250°C for 2-10 hours. Aging treatment can further optimize the microstructure of the solder, promote the uniform diffusion of alloy elements, eliminate internal stress, and improve the comprehensive properties of the solder such as strength, hardness and toughness, so that it can better meet application requirements.

[0048] After post-processing, non-destructive testing technology (such as X-ray diffraction testing) is used to conduct comprehensive quality inspection of the product to ensure that there are no defects inside the product and that the performance meets high standards. For qualified products, precise cutting and vacuum packaging are carried out to obtain the final high-performance aluminum-based brazing material. For unqualified products, they are accurately classified and returned to the corresponding process for adjustment or scrapping.

[0049] Compared with the prior art, the preparation method proposed in the present invention obtains a high-performance aluminum-based solder with accurate component content, uniform element distribution and good consistency through the synergistic effect of various process links. The preparation method proposed in the present invention has a short production cycle, energy saving and consumption reduction, stable and controllable, high preparation efficiency and low preparation cost, which helps to improve the market competitiveness of materials and meet the large-scale demand in the field of high-end precision manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0051] Figure 1 This is a photo of the product obtained in Example 1 of the present invention.

[0052] Figure 2 for Figure 1 Photo of a single aluminum-based brazing filler metal.

[0053] Figure 3 for Figure 2 Photo of product shown being used for brazing. DETAILED DESCRIPTION

[0054] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0055] In the following embodiments and comparative examples, in step S1, the pretreatment operations of the silicon block, copper block, aluminum block, and lanthanum-cerium-neodymium alloy block include the following steps: cleaning the surface with a degreasing agent, drying, sanding the surface to remove the oxide layer, ethanol cleaning, and vacuum drying.

[0056] In the following examples and comparative examples, in step S2: the method for preparing an organic dispersion of a nano-enhanced phase is specifically as follows: adding powders corresponding to trace elements to ethanol containing 5wt% of polyvinyl pyrrolidone according to a stoichiometric ratio, and ultrasonically dispersing for 40 minutes to form a uniform, stable, organic dispersion with a trace element concentration of 6wt%. The method for preparing an organic dispersion of a nano-enhanced phase is specifically as follows: adding nano-alumina powder and nano-silicon carbide powder to ethanol containing 5wt% of polyvinyl pyrrolidone according to a stoichiometric ratio, and ultrasonically dispersing for 40 minutes to form a uniform, stable, organic dispersion with a nano-enhanced phase concentration of 12wt%.

[0057] In the following embodiments and comparative examples, in step S4, the post-processing operation specifically includes removing the surface oxide film, cleaning, drying under inert gas protection, and aging treatment in sequence. The specific operation of removing the surface oxide film is: first soak the thin strip in a room temperature sodium bicarbonate solution of pH 8 for 10 minutes to remove the slight oxide film on the surface. The specific operation of cleaning is: rinse with deionized water 4 times. The specific operation of drying is: low-temperature drying at 100°C under the protection of high-purity nitrogen to remove moisture. The specific operation of aging treatment can be: placing it in an oven at a temperature of 200°C for 6 hours.

[0058] It should be noted that the operations or raw materials not described in detail below all adopt conventional technical means in the art. The test operations of various properties involved in the following examples and comparative examples are all conventional test operations in the art; when the products obtained in the following examples and comparative examples are tested for yield strength, tensile strength, elongation, impact toughness and corrosion resistance, each product is tested in parallel 3 times and the test results of 3 times are recorded.

[0059] Example 1

[0060] A high-performance aluminum-based solder comprises the following components: 10wt% silicon, 5wt% copper, 0.1wt% lanthanum, 0.2wt% cerium, 0.2wt% neodymium, 0.08wt% titanium, 0.08wt% zirconium, 0.02wt% boron, 0.02wt% vanadium, 1.5wt% nano-reinforced phase, and Al remainder, wherein the nano-reinforced phase is a mixture of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 1:1.

[0061] For the above products, follow the following steps to prepare:

[0062] S1. Pre-treat silicon blocks, copper blocks, aluminum blocks, and lanthanum-cerium-neodymium alloy blocks and then accurately weigh them according to the stoichiometric ratio; ball-mill titanium powder and zirconium powder to an average particle size of 1-10 μm, and ball-mill boron powder and vanadium powder to an average particle size of 0.5-5 μm; prepare nano-alumina powder and nano-silicon carbide powder with a particle size of 1-100 nm;

[0063] S2, firstly use an arc with a current of 400-1000A and a voltage of 15-35V to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, then pour the pre-melted alloy liquid into a cooling mold, cool it at a cooling rate of 30-150°C / s to obtain a pre-alloyed ingot, then crush the pre-alloyed ingot and perform vacuum induction melting, during vacuum induction melting, first program the temperature to 750-850°C and keep it warm for 5-30min, then slowly add the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements at a rate of 0.5-6ml / min and 0.5-2ml / min respectively, start electromagnetic stirring, the stirring rate is 300-800Hz, the magnetic field strength is 0.05-0.3T, and continue to keep warm for 25-65min to obtain the solder liquid;

[0064] S3. The strip is spun by means of a rapid solidification strip-spinning device. The technical parameters of the strip-spinning are: the copper roller linear speed is 25-40 m / s, the injection pressure is 0.15-0.5 MPa, and the solder liquid superheat is 60-140°C. Finally, a solder thin strip with a thickness of 20-50 μm and a thickness tolerance within ±3 μm is obtained.

[0065] S4. Post-processing.

[0066] The product photos are as follows Figure 1 and Figure 2 As shown, when it is used for brazing, the appearance is as Figure 3 Tests have confirmed that its yield strength is 245-255MPa, tensile strength is 295-305MPa, elongation is 14.5%-15.5%, and impact toughness is ≥50J / cm 2 , corrosion resistance ≤0.05mm / a, the product has good comprehensive performance and can meet the use needs in the field of high-end precision manufacturing.

[0067] Example 2

[0068] A high-performance aluminum-based brazing material comprises the following components: 8wt% silicon, 4wt% copper, 0.2wt% lanthanum, 0.3wt% cerium, 0.3wt% neodymium, 0.12wt% titanium, 0.12wt% zirconium, 0.03wt% boron, 0.03wt% vanadium, 1.5wt% nano-enhanced phase, and Al balance, wherein the nano-enhanced phase is a mixture of nano-alumina and nano-silicon carbide in a mass ratio of 1:1. The preparation method thereof is consistent with that of Example 1.

[0069] The yield strength of the obtained product is 250-260MPa, the tensile strength is 300-310MPa, the elongation is 15%-16%, and the impact toughness is ≥52J / cm 2 , corrosion resistance ≤0.048mm / a. Compared with Example 1, all performances are improved. Obviously, increasing the amount of rare earth elements and trace elements while appropriately reducing the amount of silicon and copper added will not only not affect the performance of the solder, but also bring about further improvement of the comprehensive performance of the solder. The synergistic effect of trace elements and rare earth elements helps to reduce costs and increase efficiency.

[0070] Example 3

[0071] A high-performance aluminum-based brazing filler metal comprises the following components: 12wt% silicon, 6wt% copper, 0.3wt% lanthanum, 0.4wt% cerium, 0.5wt% neodymium, 0.16wt% titanium, 0.16wt% zirconium, 0.04wt% boron, 0.04wt% vanadium, 1.5wt% nano-enhanced phase, and Al balance, wherein the nano-enhanced phase is a mixture of nano-alumina and nano-silicon carbide in a mass ratio of 1:1. The preparation method thereof is consistent with that of Example 1.

[0072] The yield strength of the obtained product is 255-265MPa, the tensile strength is 305-315MPa, the elongation is 15.5%-16.5%, and the impact toughness is ≥55J / cm 2 , corrosion resistance performance ≤ 0.046mm / a. Compared with Example 1, all performances are significantly improved, but compared with Example 2, although there are the above, the improvement is relatively small. Considering the cost and effect of the improvement, the cost performance of the product of Example 3 is not as good as that of Example 2.

[0073] Example 4

[0074] A high-performance aluminum-based solder comprises the following components: 9wt% silicon, 4.5wt% copper, 0.15wt% lanthanum, 0.25wt% cerium, 0.2wt% neodymium, 0.1wt% titanium, 0.1wt% zirconium, 0.03wt% boron, 0.02wt% vanadium, 0.3wt% nano-reinforced phase, and Al remainder, wherein the nano-reinforced phase is a mixture of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 7:3.

[0075] S1. Pre-treat silicon blocks, copper blocks, aluminum blocks, and lanthanum-cerium-neodymium alloy blocks and then accurately weigh them according to the stoichiometric ratio; ball-mill titanium powder and zirconium powder to an average particle size of 1-10 μm, and ball-mill boron powder and vanadium powder to an average particle size of 0.5-5 μm; prepare nano-alumina powder and nano-silicon carbide powder with a particle size of 1-100 nm;

[0076] S2, firstly use an arc with a current of 1000A and a voltage of 15V to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, then pour the pre-melted alloy liquid into a cooling mold, cool it at a cooling rate of 150°C / s to obtain a pre-alloyed ingot, then crush the pre-alloyed ingot and perform vacuum induction melting, during vacuum induction melting, first program the temperature to 750°C and keep it warm for 30min, then slowly add the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements at a rate of 0.5ml / min and 2ml / min respectively, start electromagnetic stirring, the stirring rate is 300Hz, the magnetic field strength is 0.3T, and continue to keep warm for 25min to obtain the solder liquid;

[0077] S3. The strip is spun by means of a rapid solidification strip-spinning device. The technical parameters of the strip-spinning are as follows: the linear speed of the copper roller is 40 m / s, the injection pressure is 0.15 MPa, and the superheat of the solder liquid is 140°C. Finally, a solder thin strip with a thickness of 20 μm and a thickness tolerance within ±3 μm is obtained.

[0078] S4. Post-processing.

[0079] The yield strength of the obtained product is 230-240MPa, the tensile strength is 280-290MPa, the elongation is 13%-14%, and the impact toughness is ≥45J / cm 2 , corrosion resistance ≤ 0.06mm / a. The obtained product has good performance and can meet the use needs in the field of high-end precision manufacturing.

[0080] Example 5

[0081] A high-performance aluminum-based solder comprises the following components: 11wt% silicon, 5.5wt% copper, 0.2wt% lanthanum, 0.25wt% cerium, 0.25wt% neodymium, 0.12wt% titanium, 0.12wt% zirconium, 0.03wt% boron, 0.02wt% vanadium, 1wt% nano-reinforced phase, and Al remainder, wherein the nano-reinforced phase is a mixture of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 3:7.

[0082] For the above products, follow the following steps to prepare:

[0083] S1. Pre-treat silicon blocks, copper blocks, aluminum blocks, and lanthanum-cerium-neodymium alloy blocks and then accurately weigh them according to the stoichiometric ratio; ball-mill titanium powder and zirconium powder to an average particle size of 1-10 μm, and ball-mill boron powder and vanadium powder to an average particle size of 0.5-5 μm; prepare nano-alumina powder and nano-silicon carbide powder with a particle size of 1-100 nm;

[0084] S2, firstly use an arc with a current of 400A and a voltage of 35V to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, then pour the pre-melted alloy liquid into a cooling mold, cool it at a cooling rate of 30°C / s to obtain a pre-alloyed ingot, then crush the pre-alloyed ingot and perform vacuum induction melting, during vacuum induction melting, first program the temperature to 850°C and keep it warm for 5min, then slowly add the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements at a rate of 6ml / min and 0.5ml / min respectively, start electromagnetic stirring, the stirring rate is 800Hz, the magnetic field strength is 0.05T, and continue to keep warm for 65min to obtain the solder liquid;

[0085] S3. The strip is spun through the rapid solidification strip-spinning equipment. The technical parameters of the strip-spinning are: the copper roller linear speed is 25 m / s, the injection pressure is 0.5 MPa, and the solder liquid superheat is 60°C. Finally, a solder thin strip with a thickness of 50 μm and a thickness tolerance within ±3 μm is obtained.

[0086] S4. Post-processing.

[0087] The yield strength of the obtained product is 252-262MPa, the tensile strength is 308-318MPa, the elongation is 15.2%-16.2%, and the impact toughness is ≥53J / cm 2 , corrosion resistance performance ≤ 0.047mm / a. The obtained product has good performance and can meet the use needs in the field of high-end precision manufacturing.

[0088] Example 6

[0089] A high-performance aluminum-based solder comprises the following components: 13wt% silicon, 5wt% copper, 0.3wt% lanthanum, 0.35wt% cerium, 0.35wt% neodymium, 0.14wt% titanium, 0.14wt% zirconium, 0.04wt% boron, 0.04wt% vanadium, 2wt% nano-reinforced phase, and Al balance, wherein the nano-reinforced phase is a mixture of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 4:6.

[0090] For the above products, follow the following steps to prepare:

[0091] S1. Pre-treat silicon blocks, copper blocks, aluminum blocks, and lanthanum-cerium-neodymium alloy blocks and then accurately weigh them according to the stoichiometric ratio; ball-mill titanium powder and zirconium powder to an average particle size of 1-10 μm, and ball-mill boron powder and vanadium powder to an average particle size of 0.5-5 μm; prepare nano-alumina powder and nano-silicon carbide powder with a particle size of 1-100 nm;

[0092] S2, first use an arc with a current of 1000A and a voltage of 20V to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, then pour the pre-melted alloy liquid into a cooling mold, cool it at a cooling rate of 30°C / s to obtain a pre-alloyed ingot, then crush the pre-alloyed ingot and perform vacuum induction melting, during vacuum induction melting, first program the temperature to 850°C and keep it warm for 25min, then slowly add the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements at a rate of 0.5ml / min and 2ml / min respectively, start electromagnetic stirring, the stirring rate is 600Hz, the magnetic field strength is 0.05T, and continue to keep warm for 65min to obtain the solder liquid;

[0093] S3. The strip is spun through a rapid solidification strip-spinning device. The technical parameters of the strip-spinning are: the copper roller linear speed is 30 m / s, the injection pressure is 0.15 MPa, and the solder liquid superheat is 140°C. Finally, a solder thin strip with a thickness of 30 μm and a thickness tolerance within ±3 μm is obtained.

[0094] S4. Post-processing.

[0095] The yield strength of the obtained product is 258-268MPa, the tensile strength is 312-322MPa, the elongation is 15.8%-16.8%, and the impact toughness is ≥56J / cm 2 , corrosion resistance ≤ 0.045mm / a. The obtained product has good performance and can meet the use needs in the field of high-end precision manufacturing.

[0096] Example 7

[0097] A high-performance aluminum-based brazing filler metal comprises the following components: 10wt% silicon, 7wt% copper, 0.4wt% lanthanum, 0.5wt% cerium, 0.6wt% neodymium, 0.16wt% titanium, 0.16wt% zirconium, 0.05wt% boron, 0.05wt% vanadium, 3wt% nano-reinforced phase, and Al remainder, wherein the nano-reinforced phase is a mixture of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 6:4.

[0098] For the above products, follow the following steps to prepare:

[0099] S1. Pre-treat silicon blocks, copper blocks, aluminum blocks, and lanthanum-cerium-neodymium alloy blocks and then accurately weigh them according to the stoichiometric ratio; ball-mill titanium powder and zirconium powder to an average particle size of 1-10 μm, and ball-mill boron powder and vanadium powder to an average particle size of 0.5-5 μm; prepare nano-alumina powder and nano-silicon carbide powder with a particle size of 1-100 nm;

[0100] S2, firstly use an arc with a current of 400A and a voltage of 35V to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, then pour the pre-melted alloy liquid into a cooling mold, cool it at a cooling rate of 80°C / s to obtain a pre-alloyed ingot, then crush the pre-alloyed ingot and perform vacuum induction melting, during vacuum induction melting, first program the temperature to 750°C and keep it warm for 30min, then slowly add the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements at a rate of 1ml / min and 0.5ml / min respectively, start electromagnetic stirring, the stirring rate is 800Hz, the magnetic field strength is 0.25T, and continue to keep warm for 25min to obtain the solder liquid;

[0101] S3. The strip is spun through a rapid solidification strip-spinning device. The technical parameters of the strip-spinning are: the copper roller linear speed is 40 m / s, the injection pressure is 0.4 MPa, and the solder liquid superheat is 60°C. Finally, a solder thin strip with a thickness of 50 μm and a thickness tolerance within ±3 μm is obtained.

[0102] S4. Post-processing.

[0103] The yield strength of the obtained product is 250-260MPa, the tensile strength is 300-310MPa, the elongation is 14.5%-15.5%, and the impact toughness is ≥50J / cm 2 , corrosion resistance ≤ 0.052mm / a. The obtained product has good performance and can meet the use needs in the field of high-end precision manufacturing.

[0104] Example 8

[0105] Compared with Example 1, the contents of lanthanum and neodymium are adjusted to 0.15wt%, and the rest including the preparation method is consistent with Example 1.

[0106] The yield strength of the obtained product is 246-256MPa, the tensile strength is 300-310MPa, the elongation is 14.6%-15.6%, and the impact toughness is ≥50.5J / cm 2 , corrosion resistance performance ≤ 0.047mm / a. The obtained product has good performance and can meet the use needs in the field of high-end precision manufacturing.

[0107] Example 9

[0108] Compared with Example 1, the contents of silicon, copper and nano-reinforced phase remain unchanged, and the contents of rare earth elements and trace elements are adjusted to: 0.5wt% lanthanum, 0.8wt% cerium, 0.7wt% neodymium, 0.12wt% titanium, 0.12wt% zirconium, 0.03wt% boron and 0.03wt% vanadium.

[0109] The yield strength of the obtained product is 260-270MPa, the tensile strength is 315-325MPa, the elongation is 16%-17%, and the impact toughness is ≥58J / cm 2 , corrosion resistance performance ≤ 0.044mm / a. The obtained product has good performance and can meet the use needs in the field of high-end precision manufacturing.

[0110] Example 10

[0111] Compared with Example 1, the silicon content is adjusted to 5wt%, the copper content is adjusted to 3wt%, the lanthanum content is adjusted to 0.05wt%, the cerium content is adjusted to 0.1wt%, the neodymium content is adjusted to 0.05wt%, and the titanium, zirconium, boron and vanadium are all adjusted to 0.125wt%.

[0112] Embodiment 11

[0113] Compared with Example 1, the silicon content is adjusted to 15wt%, the copper content is adjusted to 1wt%, the lanthanum content is adjusted to 0.5wt%, the cerium content is adjusted to 1wt%, and the neodymium content is adjusted to 0.5wt%.

[0114] Example 12

[0115] Compared with Example 1, the contents of lanthanum, cerium and neodymium are all adjusted to 0.5 wt %.

[0116] After testing, Examples 10, 11, and 12 can all obtain high-performance aluminum-based brazing filler metals, but their performance is not as good as that of Example 1.

[0117] Embodiment 13

[0118] Compared with Example 8, the total content of titanium and zirconium is unchanged at 0.28 wt %, but the titanium-zirconium content ratio is 1:0.6.

[0119] Embodiment 14

[0120] Compared with Example 8, the total content of titanium and zirconium is unchanged at 0.28 wt %, but the titanium-zirconium content ratio is 1:0.7.

[0121] Embodiment 15

[0122] Compared with Example 8, the total content of titanium and zirconium is unchanged at 0.28 wt %, but the titanium-zirconium content ratio is 1.5:1.

[0123] Comparing the mechanical properties of the products obtained in Example 8, Example 13, Example 14, and Example 15, the order of superiority and inferiority is: Example 15> Example 8> Example 14> Example 13. The order of superiority and inferiority of corrosion resistance is consistent with that of mechanical properties. Obviously, the titanium-zirconium content ratio has a greater influence on the mechanical properties of the solder, which is closely related to the titanium-zirconium grain refinement and the construction of high-performance microstructure.

[0124] Comparative Example 1

[0125] Compared with Example 1, no rare earth element is added, and the contents of silicon, copper, trace elements, and nano-enhanced phase are all consistent with those in Example 1, and the preparation method is also consistent with that in Example 1.

[0126] The yield strength of the obtained product is 220-230MPa, the tensile strength is 270-280MPa, the elongation is 12%-13%, and the impact toughness is ≥40J / cm 2 , corrosion resistance ≤0.07mm / a. Obviously, the lack of rare earth elements is not conducive to the wettability, oxidation resistance and joint strength of the solder, resulting in significant deterioration of the mechanical properties and corrosion resistance of the solder.

[0127] Comparative Example 2

[0128] Compared with Example 1, no cerium is added to the rare earth elements, and the contents of silicon, copper, lanthanum, neodymium, trace elements, and nano-reinforced phase are all consistent with those in Example 1, and the preparation method is also consistent with that in Example 1.

[0129] The yield strength of the obtained product is 238-248MPa, the tensile strength is 288-298MPa, the elongation is 13.8%-14.8%, and the impact toughness is ≥47J / cm 2 , corrosion resistance ≤ 0.062mm / a. Obviously, although the rare earth elements of lanthanum and neodymium have better performance than not adding any rare earth elements, they cannot reach the best state. The synergistic effect of lanthanum, cerium and neodymium can achieve the best performance.

[0130] Comparative Example 3

[0131] Compared with Example 1, an equal amount of boron and an equal amount of vanadium are added to the trace elements, titanium and zirconium are not added, and the rest including the preparation method is consistent with Example 1.

[0132] The yield strength of the obtained product is 230-240MPa, the tensile strength is 280-290MPa, the elongation is 13%-14%, and the impact toughness is ≥45J / cm 2 , corrosion resistance performance ≤0.06mm / a.

[0133] Comparative Example 4

[0134] Compared with Example 1, an equal amount of titanium and an equal amount of zirconium are added to the trace elements, and boron and vanadium are not added. The rest including the preparation method is consistent with Example 1.

[0135] The yield strength of the obtained product is 240-250MPa, the tensile strength is 290-300MPa, the elongation is 14%-15%, and the impact toughness is ≥48J / cm 2 , corrosion resistance performance ≤0.055mm / a.

[0136] Comparative Example 5

[0137] Compared with Example 1, equal amounts of vanadium, titanium and zirconium are added to the trace elements, and no boron is added. The rest including the preparation method is consistent with Example 1.

[0138] The yield strength of the obtained product is 238-248MPa, the tensile strength is 288-298MPa, the elongation is 13.8%-14.8%, and the impact toughness is ≥47J / cm 2 , corrosion resistance performance ≤0.062mm / a.

[0139] Comparative Example 6

[0140] Compared with Example 1, no trace elements are added, and the rest including the preparation method is consistent with Example 1.

[0141] The yield strength of the obtained product is 220-224MPa, the tensile strength is 260-265MPa, the elongation is 12.2%-12.5%, and the impact toughness is ≥43J / cm 2 , corrosion resistance performance ≤0.062mm / a.

[0142] Comparison of Example 1 with Comparative Examples 3, 4, 5 and 6 shows that the addition of four trace elements simultaneously has a significant effect on the mechanical properties, spreadability and corrosion resistance of the solder. Moreover, titanium and zirconium have a particularly significant effect on the above properties, while boron and vanadium have a relatively smaller effect. This is probably related to the fact that the combination of titanium and zirconium in a limited ratio helps to refine the grains of the solder and enhance its corrosion resistance and mechanical properties.

[0143] Comparative Example 7

[0144] Compared with Example 1, the silicon content is adjusted to 3wt%, the copper content is adjusted to 10wt%, and the rest including the preparation method is consistent with Example 1.

[0145] The yield strength of the obtained product is 210-220MPa, the tensile strength is 260-270MPa, the elongation is 11%-12%, and the impact toughness is ≥35J / cm 2 , corrosion resistance performance ≤0.08mm / a.

[0146] Comparative Example 8

[0147] Compared with Example 1, the copper content was adjusted to 10 wt %, and the rest including the preparation method was consistent with Example 1.

[0148] The yield strength of the obtained product is 225-235MPa, the tensile strength is 275-285MPa, the elongation is 12.5%-13%, and the impact toughness is ≥42J / cm 2 , corrosion resistance performance ≤0.068mm / a.

[0149] Comparing Comparative Examples 7 and 8 with Example 1, it can be seen that when the silicon and copper contents deviate from the reasonable range, various properties are significantly reduced, which further illustrates the key influence of silicon and copper contents on the performance of the solder.

[0150] In summary: the present invention optimizes the types and proportions of the components in the aluminum-based solder and synergizes them through a scientifically designed preparation method to obtain a high-performance aluminum-based solder with good comprehensive performance, which can meet the needs of the high-end precision manufacturing field. The product is lightweight, environmentally friendly and recyclable. The preparation method has low energy consumption, short preparation cycle, high efficiency and high repeatability. It is highly competitive in the market and worthy of large-scale and industrial application.

[0151] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A high performance aluminum-based brazing filler metal, characterized in that: The composition comprises the following contents: 5-15wt% silicon, 1-8wt% copper, 0.2-2wt% rare earth elements, 0.02-0.5wt% trace elements, 0.3-3wt% nano-enhanced phase, and Al balance; The rare earth element is a combination of lanthanum, cerium and neodymium; The trace elements are a combination of titanium, zirconium, boron and vanadium, with a titanium-zirconium content ratio of 1:(0.5-1) and a boron-vanadium content ratio of 1:(0.3-2); The nano-reinforced phase is a composition of nano-aluminum oxide and nano-silicon carbide, and the content of nano-aluminum oxide in the nano-reinforced phase is 30-70wt%.

2. The high performance aluminum-based brazing filler metal according to claim 1, characterized in that: The composition comprises the following contents: 8-12wt% silicon, 3-6wt% copper, 0.5-1.5wt% rare earth elements, 0.15-0.5wt% trace elements, 1-2wt% nano-enhanced phase, and Al balance; Among the rare earth elements, the content ratio of lanthanum, cerium and neodymium is (2-3):(3-4):(2-3); Among the trace elements, the total content of titanium and zirconium is 0.2-0.4wt%, the total content of boron and vanadium is 0.1-0.3wt%, and the content ratio of titanium and zirconium is 1:(0.6-0.7), and the content ratio of boron and vanadium is 1:(0.9-1.1).

3. The high performance aluminum-based brazing filler metal according to claim 2, characterized in that: Among the trace elements, the ratio of titanium to zirconium is 1.5:1, and the ratio of boron to vanadium is 1:

1.

4. The high performance aluminum-based brazing filler metal according to claim 1, characterized in that: The rare earth element content is 0.5-1.2wt%, the total titanium-zirconium content is 0.3-0.45wt%, and the titanium-zirconium content ratio is 1:(0.8-0.9).

5. The high performance aluminum-based brazing filler metal according to claim 1, characterized in that: The copper content is 5-7wt%.

6. The high performance aluminum-based brazing filler metal according to any one of claims 1 to 5, characterized in that: The nano-reinforced phase is a composite of nano-aluminum oxide and nano-silicon carbide in a mass ratio of 1:1, and the average particle sizes of the nano-aluminum oxide and the nano-silicon carbide are both 10-100nm.

7. A method for preparing a high-performance aluminum-based brazing filler metal according to any one of claims 1 to 6, characterized in that: The method comprises the following operation steps: S1, raw material preparation; S2, composite smelting; S3, strip throwing; S4, post-processing.

8. The preparation method according to claim 7, characterized in that: In step S1, The sources of silicon, copper and aluminum are silicon blocks, copper blocks and aluminum blocks respectively; the source of rare earth elements is lanthanum-cerium-neodymium alloy blocks; the source of trace elements is titanium powder, zirconium powder, boron powder and vanadium powder; the source of nano-reinforcement phase is nano-alumina powder and nano-silicon carbide powder; Silicon blocks, copper blocks, aluminum blocks, and lanthanum-cerium-neodymium alloy blocks are pretreated first and then accurately weighed according to the stoichiometric ratio. The pretreatment includes a treatment to improve the purity of the raw materials and / or a treatment to activate the surface state of the raw materials.

9. The preparation method according to claim 7, characterized in that: In step S2, the composite smelting includes arc melting and vacuum induction melting. First, an arc with a current of 400-1000A and a voltage of 15-35V is used to melt the remaining raw materials except the trace elements and the nano-enhanced phase to obtain a pre-melted alloy liquid, and then the pre-melted alloy liquid is poured into a cooling mold, cooled at a cooling rate of 30-150°C / s to obtain a pre-alloyed ingot, and then the pre-alloyed ingot is crushed and vacuum induction melting is performed. During the vacuum induction melting, the temperature is first raised to 750-850°C and kept warm for 5-30min, and then the organic dispersion of the nano-enhanced phase and the organic dispersion of the trace elements are slowly added in sequence, and electromagnetic stirring is turned on, the stirring rate is 300-800Hz, the magnetic field strength is 0.05-0.3T, and the temperature is kept warm for 25-65min to obtain the solder liquid; The organic dispersion of the nano-reinforced phase and the organic dispersion of the trace elements are obtained by ultrasonically dispersing the nano-reinforced phase and the trace elements in an organic solvent, respectively. The organic solvent contains only C, H and O elements.

10. The preparation method according to claim 7, characterized in that: In step S3, the strip is spun by a rapid solidification strip spun device, and the technical parameters of the strip spun are: the copper roller linear speed is 25-40 m / s, the injection pressure is 0.15-0.5 MPa, and the solder liquid superheat is 60-140° C., and finally a solder thin strip with a thickness of 20-50 μm and a thickness tolerance within ±3 μm is obtained; In step S4, the post-treatment includes: removing the surface oxide film, cleaning, drying under vacuum or inert gas protection and aging treatment, and the temperature of the aging treatment is 120-250° C. and the time is 2-10 hours.

Citation Information

Patent Citations

  • Brazing material for bonding in atmosphere, bonded article, and current collecting material

    CN102883853A

  • High-aluminium and high-silicon cast titanium alloy

    CN104018028A

  • Foil strip brazing filler metal for brazing sintered neodymium-iron-boron permanent magnet materials and preparation method

    CN111151916A

  • Moderate-temperature Zr-based brazing filler metal special for Ti2AlNb-based alloy identical or different material brazing and preparation method and brazing process of brazing filler metal

    CN111702281A

  • Aluminum-based composite material and preparation method thereof

    CN118880094A

Cited By

  • Al-Si-Cu-Mg corrosion-resistant low-temperature brazing filler metal with low copper content and preparation method thereof

    CN121423907A